Profile of students and professors of health courses at a federal institution in the Northeastern Brazil (Research, Society and Development, 2022)
Objective: To describe the profile of students and professors of undergraduate courses in health sciences at an institution in Northeastern Brazil. Methods: It consists of a cross-sectional, descriptive and quantitative study that used a questionnaire available online, developed by the researchers and validated by the Face Validity method. The questionnaire was applied between March and June 2020. Results: 123 students and 36 professors participated in the research. Considering the students, 81.3% were female, 62.6% declared themselves brown, 79.6% were aged between 18 and 22 years. In addition, 95.9% had previous pedagogical experience with traditional teaching. considering the teachers, 69.4% were female, 50% declared themselves white and 27.8% were aged between 30 and 34 years. In addition, 61.1% studied at private educational institutions, 66.7% were doctors and 75% had previous pedagogical experience with traditional teaching. Conclusion: It is possible to observe that the profile of students and teachers described is heterogeneous and may portray the educational and socioeconomic context in which individuals from this higher education institution are involved.